DYNAMIC TURNING SYSTEM INSTABILITY THROUGH POSITIONAL COUPLING OF TREATMENT PROCESS - Vilor L. Zakovorotniy; Dinh Tung Pham; Xuan Chiem Nguyen (Advanced Engineering Research, 2011)
The problem of the dynamic cutting system instability through the positional coupling which is formed as a result of the cutting force change depending on the elastic deformation displacements of the tool in relation to the workpiece, is considered. The cutting instability dependency on the skew-symmetric components of the system total stiffness matrix which form circulation (nonpotential) forces is shown.